2006
DOI: 10.1029/2005jc002996
|View full text |Cite
|
Sign up to set email alerts
|

Continuum sea ice rheology determined from subcontinuum mechanics

Abstract: [1] A method is presented to calculate the continuum-scale sea ice stress as an imposed, continuum-scale strain-rate is varied. The continuum-scale stress is calculated as the areaaverage of the stresses within the floes and leads in a region (the continuum element). The continuum-scale stress depends upon: the imposed strain rate; the subcontinuum scale, material rheology of sea ice; the chosen configuration of sea ice floes and leads; and a prescribed rule for determining the motion of the floes in response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
(35 reference statements)
1
8
0
Order By: Relevance
“…[70] Moreover, the deformation rates estimated by both models agree with the observations at large spatial scales (100-300 km), suggesting that all the variability regarding sea ice deformation below such scales is missing in both models, regardless of their high resolution ($10 km grid size). This is consistent with the conclusions of Taylor et al [2006] who suggested that the adoption of isotropic, continuum rheology at sub-100 km resolutions is not useful for a more detailed prediction of ice dynamics.…”
Section: Scaling Properties Of Sea Ice Deformationsupporting
confidence: 91%
“…[70] Moreover, the deformation rates estimated by both models agree with the observations at large spatial scales (100-300 km), suggesting that all the variability regarding sea ice deformation below such scales is missing in both models, regardless of their high resolution ($10 km grid size). This is consistent with the conclusions of Taylor et al [2006] who suggested that the adoption of isotropic, continuum rheology at sub-100 km resolutions is not useful for a more detailed prediction of ice dynamics.…”
Section: Scaling Properties Of Sea Ice Deformationsupporting
confidence: 91%
“…Taylor et al . [] took a somewhat different approach: they calculated relative floe motion using the kinematic model of UM but calculated sea ice stress from a consideration of the deformation of the ice in the leads separating the floes and using the mean stress theorem to calculate the large‐scale sea ice stress from the integral of edge tractions. This approach allowed an investigation of the scale‐dependence of sea ice rheology and the (restrictive) conditions under which the ice cover could be considered isotropic.…”
Section: The Anisotropic Modelmentioning
confidence: 99%
“…Wilchinsky and Feltham [] generalized the Taylor et al . [] approach to calculate the anisotropic sea ice stress associated with an idealized sea ice cover consisting of closely interlocking, diamond‐shaped ice floes delineated by slip lines. This underlying anisotropic tiling of the sea ice cover is supported by observations (Figure ) and was also shown to emerge through discrete element simulations of the sea ice [ Wilchinsky et al ., ].…”
Section: The Anisotropic Modelmentioning
confidence: 99%
“…In particular, the elastic-decohesive (Schreyer et al 2006;Sulsky and Paterson 2011) and the elasto-brittle (Girard et al 2011) models focus on the process of the crack formation and corresponding weakening of the sea ice without explicitly addressing their postfailure dynamics. In order for an isotropic model to be able to represent the effect of anisotropically distributed leads, the model resolution should be much smaller than the dimensions of the leads, which is generally not the case, and the rheology of sea ice should be isotropic with known scale dependence (Feltham 2008, supplemental appendix C; Taylor et al 2006).…”
Section: Introductionmentioning
confidence: 99%